2000
DOI: 10.1038/35018247
|View full text |Cite
|
Sign up to set email alerts
|

Tangled tale of a lost, stolen and disputed coelacanth

Abstract: in many areas, including the biological and physical sciences. The government has not yet said how much extra money will be available to cover the increases, leading some to fear that student numbers could fall. Earlier this year the life-science community called for a pay increase, even if it meant cutting back on numbers (see Nature 403, 347; 2000). But the Treasury has denied that this is their intention. A spokesperson said the aim was to have more and better research students, and that "this does not mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Over the last 10–15 years there have been a few highly public instances of falsified images (Abbott 1997; Aldhous and Reich 2009; Bagley 2009; Greenberg 1996; Katsnelson 2007; McCabe and Wright 2000; Normile 2009; Rolph and McNerthney 2007; Rossner 2006; Vogel 2006, 2008; Weissmann 2006; Xin 2006; Young 2008), but most of the problem lies with the lack of a basic understanding of how to properly handle image data. Graduate student training often includes a mandatory ethics class (students supported by NIH training grants are required to receive responsible conduct of research training, NIH 1994, 2009) and many of these courses now include discussion of the Rossner and Yamada paper (2004).This is a good start, but until students (and their more established colleagues) understand the reasoning behind the detailed instructions to authors found in many journals, these instructions will continue to be poorly understood and compliance will suffer.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last 10–15 years there have been a few highly public instances of falsified images (Abbott 1997; Aldhous and Reich 2009; Bagley 2009; Greenberg 1996; Katsnelson 2007; McCabe and Wright 2000; Normile 2009; Rolph and McNerthney 2007; Rossner 2006; Vogel 2006, 2008; Weissmann 2006; Xin 2006; Young 2008), but most of the problem lies with the lack of a basic understanding of how to properly handle image data. Graduate student training often includes a mandatory ethics class (students supported by NIH training grants are required to receive responsible conduct of research training, NIH 1994, 2009) and many of these courses now include discussion of the Rossner and Yamada paper (2004).This is a good start, but until students (and their more established colleagues) understand the reasoning behind the detailed instructions to authors found in many journals, these instructions will continue to be poorly understood and compliance will suffer.…”
Section: Discussionmentioning
confidence: 99%
“…Research that has been published on Pangandaran prior to the tsunami focused on the vegetation of the nature reserve (e.g., Sumardja and Kartawinata 1977), its wildlife, and, in particular, the population of the endemic ebony langurs ( Trachypithecus auratus ; e.g., Kool 1993) and, briefly, on a coelacanth ( Latimeria menadoensis ) that had allegedly been caught in the Bay of Pangandaran in 1995 (Erdmann and Caldwell 2000; McCabe and Wright 2000). Not surprisingly, post-tsunami research focused heavily on the disaster and its aftermath (e.g., Fritz et al 2007; Lavigne et al 2007; Reese et al 2007) and, to a lesser extent, wildlife and fisheries (Nurhayati and Purnomo 2014; Tsuji et al 2013).…”
Section: Methodsmentioning
confidence: 99%
“…To substantiate this claim, a report was sent to the journal Nature containing a digitized photograph. At the time of printing, it was noticed that the white dot patterns of the two fish were identical (McCabe & Wright, 2000). These dot patterns are unique, like genetic fingerprints.…”
Section: Coelacanth Heritagementioning
confidence: 99%